Forecast-planning system of financial support for the development of industrial enterprises - Lytvyn, Inna; Fesenko, Maryna; Hurman, Olena; Nahorniak, Halina; Kuzmenko, Оksana (My University, 2022)
The aim of the article is to develop a forecast planned system of financial support for enterprise development based on approaches to forecasting factors influencing the need for financial resources to ensure enterprise development and planning financial support for enterprise development. In order to ensure high quality and accurate forecasting of external and internal environmental factors necessary for further planning and the possibility of sound planning, the system has formed forecasting and planning modules. Based on the structure of the forecasting module with the identification of key factors influencing the financial security of the enterprise and comparing the most effective forecasting methods, an approach to forecasting factors influencing the need for financial resources in ensuring the development of agricultural machinery. The forecasting module is built by combining quantitative forecasting methods based on the approximation of existing trends with quantitative and qualitative approaches based on expert assessments. Based on a combination of balance, calculation analytical and program-target planning and formalization of the choice of the date of the beginning of measures to manage financial security depending on the importance of the event, an approach to planning financial support for enterprise development. In the planning module, the external element in relation to the financial management system is the goal-setting system of the enterprise, which determines the mission and its goals in the areas of development. Approbation of the forecast-planning system at PJSC "Harvesters" was carried out. The results would be useful for practitioners, for the effective implementation of sustainable planning and forecasting of enterprise resources in accordance with the objectives of its development. Метою статті є розробка прогнозної планової системи фінансового забезпечення розвитку підприємства на основі підходів до прогнозування факторів впливу на потребу у фінансових ресурсах для забезпечення розвитку підприємства та планування фінансового забезпечення розвитку підприємства. Для забезпечення якісного та точного прогнозування факторів зовнішнього та внутрішнього середовища, необхідних для подальшого планування та можливості обґрунтованого планування, в системі сформовано модулі прогнозування та планування. На основі структури модуля прогнозування з визначенням ключових факторів, що впливають на фінансову безпеку підприємства та порівнянням найбільш ефективних методів прогнозування, запропоновано підхід до прогнозування факторів, що впливають на потребу у фінансових ресурсах у забезпеченні розвитку сільськогосподарського машинобудування. Модуль прогнозування побудований шляхом поєднання кількісних методів прогнозування на основі апроксимації існуючих тенденцій з кількісними та якісними підходами на основі експертних оцінок. На основі поєднання балансового, розрахунково-аналітичного та програмно-цільового планування та формалізації вибору дати початку заходів з управління фінансовою безпекою залежно від важливості події запропоновано підхід до планування фінансового забезпечення розвитку підприємства. У модулі планування зовнішнім елементом по відношенню до системи управління фінансами є система цілепокладання підприємства, яка визначає місію та його цілі за напрямами розвитку. Проведено апробацію прогнозно-планової системи на ПАТ «Комбайни». Результати будуть корисними для практиків, для ефективного впровадження сталого планування та прогнозування ресурсів підприємства відповідно до цілей його розвитку.
Keywords: кафедра міжнародної економіки; agricultural engineering; forecasting; financial support; enterprise development; планування; сільськогосподарська інженерія; прогнозування; фінансова підтримка; фінансова підтримка; розвиток підприємництва